Student atlas - Dorling Kindersley Cartography (Firm); DK Publishing, Inc.; Dorling Kindersley Limited (New York : DK Publishing, 2002)
Maps, illustrations, and text describe various aspects of countries of the world including physical features, population, standards of living, natural resources, industries, environmental issues, and climate.
"Copyright 1998, 2002 Dorling Kindersley Limited, London"--T.p. verso.
Includes index.
Keywords: Children's atlases; Atlases